2018
DOI: 10.1111/ssqu.12476
|View full text |Cite
|
Sign up to set email alerts
|

Gun Talk Online: Canadian Tools, American Values*

Abstract: Objective The objective of this study is to address the following question: Why has the United States been so reluctant to embrace the type of comprehensive gun control that is in place in every other developed democracy? Method The method used to address this question is a computerized content analysis on nearly 18 million words that were extracted from online political discussions of Canadian and American gun enthusiasts. A comparison of these discussions was guided by three theories on the character and ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
3
14
0
1
Order By: Relevance
“…While deference to authority has declined in Canada, as in other industrialized nations, in many respects, Canadian values are closer to European values, with the United States more the outlier or laggard nation (Nevitte 1996). While Lipset’s thesis has its critics (see, for example, Conway 1991; Grabb and Curtis 2005; Grabb, Curtis, and Baer 2000; Kaufman 2009; Tyrrell 1991), its interpretation is consistent with the findings of this analysis, and other studies (McLean 2018) that reported divergent framing of “gun talk” on the social media by firearms owners in Canada as compared with the United States.…”
Section: Resultssupporting
confidence: 84%
“…While deference to authority has declined in Canada, as in other industrialized nations, in many respects, Canadian values are closer to European values, with the United States more the outlier or laggard nation (Nevitte 1996). While Lipset’s thesis has its critics (see, for example, Conway 1991; Grabb and Curtis 2005; Grabb, Curtis, and Baer 2000; Kaufman 2009; Tyrrell 1991), its interpretation is consistent with the findings of this analysis, and other studies (McLean 2018) that reported divergent framing of “gun talk” on the social media by firearms owners in Canada as compared with the United States.…”
Section: Resultssupporting
confidence: 84%
“…This is an instance of the conservative most sacred value because if provided by God, gun rights are then a sacred tradition needed to sustain a moral community. This reaffirms qualitative work on guns as a "right" (McLean 2018).…”
Section: Methodssupporting
confidence: 68%
“…In this vein, McLean (2018) confirms Lipset’s (1989) analysis of how the differences in values between Canadians and Americans shape variation in attitudes about guns between the two nations. In particular, McLean (2018) finds that much of this variation can be traced to American gun enthusiasts’ attitudes about gun culture being rooted in American values of individual liberty and aversion to government.…”
Section: Theory and Literature Reviewmentioning
confidence: 69%
See 2 more Smart Citations